Bulk NiTiCuCo shape memory alloys with ultra-high thermal and superelastic cyclic stability. (15th July 2021) - Ahadi, Aslan; Ghorabaei, Amir Sabet; Shirazi, Hassan; Nili-Ahmadabadi, Mahmoud
Abstract : Shape memory alloys sustaining stable functional properties for millions of cycles have been reported in NiTiCuCo thin films. The mechanism behind such ultralow functional fatigue was proposed to originate from the epitaxy strains surrounding coherent Ti2 Cu precipitates. Despite having a well-understood microstructural origin, such fatigue-resistant property has never been achieved in bulk NiTiCuCo counterparts. In this study, we first show that the semi-coherent Ti2 Cu precipitates help satisfy closely the compatibility criteria under thermal phase transformation. Assisted by aging at 600 °C for 1 h, an unprecedented thermal stability is reported in bulk coarse-grained Ti54 Ni31.7 Cu12.3 Co2, where the transformation temperatures migrate by ∼ 0.1 °C for 200 cycles. To achieve stable superelastic response, a thermomechanical processing route is proposed that results in a uniform nanocrystalline microstructure with embedded Ti2 Cu precipitates. Such a microstructure exhibits much improved superelastic cyclic stability as evidenced by ∼ 22 MPa shakedown of plateau stress for 200 superelastic cycles. Graphical abstract: Image, graphical abstract